Past participle agreement a study on the grammaticalization of formal features - Vega Vilanova, Jorge (Linguistik aktuell ;, 2020)
"In this book, the traditional definition of 'grammaticalization' is challenged in the light of current developments in grammar theory. The main innovation of this approach is the focus on the feature composition of lexical items. From this perspective, the loss of past participle agreement in Catalan is analyzed on the basis of newly collected data as a consequence of the grammaticalization of formal features. The emergence of syntactic formal features through grammaticalization is understood as a last-resort repair mechanism for pragmatically costly derivations. Further far-reaching implications of this proposal under discussion are: the interplay between (re-)parametrization, economy, cyclicity and grammaticalization; the characterization of free variation under a modified version of the Interface Hypothesis; and the precedence of syntactic over morphological change. This book is not only of interest to specialists in Romance languages but also to anyone working on diachronic linguistics"--